1992
DOI: 10.1007/bf00317789
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic ants as an alternative defense against giraffe herbivory in spinescent Acacia drepanolobium

Abstract: We explore here the occurrence of aggressive ants in an apparently symbiotic relationship with the savanna tree Acacia drepanolobium and their effects on giraffe herbivory on the Athi-Kapiti Plains, Kenya. Trees taller than 1.3 m were more likely to be occupied by aggressive ants in the genus Crematogaster than were shorter trees. Ants wereconcentrated on shoot tips, the plant parts preferred by giraffes. Trees with relatively more foliage had more swarming ants than did trees with less foliage. The feeding be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 16 publications
4
99
0
Order By: Relevance
“…In such cases, the presence of ants foraging on fruits may be nonfunctional, as ants may be inefficient in defending the host plant against some vertebrates (Ho¨lldobler & Wilson 1990;Stapley 1998;Rico-Gray & Oliveira 2007). Moreover, in some cases, the presence of ants may even be undesirable, as they may frighten some possible disperses (Madden & Young 1992;Stapley 1998;Thomas 1988). A recent study performed by Yamawo et al (2012b) showed that the plants can gradually shift from direct to indirect defense against herbivory during leaf aging.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, the presence of ants foraging on fruits may be nonfunctional, as ants may be inefficient in defending the host plant against some vertebrates (Ho¨lldobler & Wilson 1990;Stapley 1998;Rico-Gray & Oliveira 2007). Moreover, in some cases, the presence of ants may even be undesirable, as they may frighten some possible disperses (Madden & Young 1992;Stapley 1998;Thomas 1988). A recent study performed by Yamawo et al (2012b) showed that the plants can gradually shift from direct to indirect defense against herbivory during leaf aging.…”
Section: Discussionmentioning
confidence: 99%
“…Some thorns have swollen bases that con¯uence into large hollow pseudo-galls (hereafter galls), which are red when young and fade to black and grey-white when old. Obligate ants (Crematogaster nigriceps, C. sjostedti, C. mimosae, and Tetraponera penzigi) (Madden and Young, 1992;Young et al, 1997), occupy these swollen thorns.…”
Section: The Speciesmentioning
confidence: 99%
“…However, its utilization by herbivores is hampered by the presence of ants that live in its galls. Together with the thorns (Milewski et al, 1991), the ants are believed to ward off herbivores by their stings and bites and to irritate feeding herbivores (Madden and Young, 1992;Young et al, 1997).…”
Section: The Speciesmentioning
confidence: 99%
“…The efficiency of herbivore exclusion by ants is mainly influenced by two factors related to ant activities, namely the encounter rate of ants with herbivores on the plant and the ant aggressiveness against the herbivores (Letourneau, 1983;Madden and Young, 1992;Rocha and Bergallo, 1992;Gaume et al, 1997). The encounter rate of ants with herbivores on a plant depends on the number of ants visiting the plant and the foraging patterns of the ants on the plant .…”
Section: Introductionmentioning
confidence: 99%